A Multicultural Counseling Approach In A Plural Society - Annisyah, Fitry (Journal of Innovation in Research, Education and Culture (JIREC), 2024)
The aim of this research is to determine multicultural counseling approaches in a pluralistic society. The research method used is a qualitative method with data collection techniques, namely literature studies sourced from books and journals. The results obtained from this research show that multicultural counseling is very helpful for problems that occur in pluralistic societies with various ethnicities, races, religions and cultures. So it can be concluded that multicultural counseling must be able to understand the cultural characteristics of a pluralistic society. Keyword: Counseling, Multicultural, Plural